Moving Bodies, Navigating Conflict : Practicing Bharata Natyam in Colombo, Sri Lanka - Satkunaratnam, Ahalya (Book collections on Project MUSE., 2020)
"Moving Bodies, Navigating Conflict is a performance-ethnographic examination of the ways in which dance embodies the physical, emotional, and social landscapes of Sri Lanka's civil war between the Sri Lankan government and the rebel separatists, the Tamil Tigers"--